2020
DOI: 10.1158/2159-8290.cd-20-0652
|View full text |Cite
|
Sign up to set email alerts
|

MNK Inhibition Sensitizes KRAS-Mutant Colorectal Cancer to mTORC1 Inhibition by Reducing eIF4E Phosphorylation and c-MYC Expression

Abstract: KRAS-mutant colorectal cancers (CRC) are resistant to therapeutics, presenting a significant problem for ~40% of cases. Rapalogs, which inhibit mTORC1 and thus protein synthesis, are significantly less potent in KRAS-mutant CRC. Using Kras-mutant mouse models and mouse-and patient-derived organoids we demonstrate that KRAS with G12D mutation fundamentally rewires translation to increase both bulk and mRNA-specific translation initiation. This occurs via the MNK/eIF4E pathway culminating in sustained expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 73 publications
0
48
0
Order By: Relevance
“…In the short-term hyperproliferation model, the inactivation of Eef2k completely reversed the suppression of proliferation seen in Apc fl/fl Kras G12D/+ Rpl24 Bst/+ small intestines ( Figure 5A–C ), and the medial colon ( Figure 5—figure supplement 1A ). The kinase inactive Eef2k allele resulted in P-eEF2 being undetectable ( Figure 5C and Figure 2—figure supplement 1 ), and we previously reported no difference in hyperproliferation between Apc fl/fl Kras G12D/+ and Apc fl/fl Kras G12D/+ Eef2k D273A/D273A models ( Knight et al, 2020a ). The reversal in proliferation rate with Eef2k and Rpl24 Bst mutations was also seen in intestinal organoid growth after 3 days ( Figure 5D ).…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…In the short-term hyperproliferation model, the inactivation of Eef2k completely reversed the suppression of proliferation seen in Apc fl/fl Kras G12D/+ Rpl24 Bst/+ small intestines ( Figure 5A–C ), and the medial colon ( Figure 5—figure supplement 1A ). The kinase inactive Eef2k allele resulted in P-eEF2 being undetectable ( Figure 5C and Figure 2—figure supplement 1 ), and we previously reported no difference in hyperproliferation between Apc fl/fl Kras G12D/+ and Apc fl/fl Kras G12D/+ Eef2k D273A/D273A models ( Knight et al, 2020a ). The reversal in proliferation rate with Eef2k and Rpl24 Bst mutations was also seen in intestinal organoid growth after 3 days ( Figure 5D ).…”
Section: Resultsmentioning
confidence: 57%
“…Evidence suggests that targeting translation in KRAS -mutant CRC can be effective. As well as our recent study re-sensitising Kras -mutant CRCs to rapamycin by targeting translation initiation ( Knight et al, 2020a ), we have demonstrated that Kras -mutant models of CRC depend upon the transporter SLC7A5 to maintain protein synthesis by facilitating the influx of amino acids ( Najumudeen et al, 2021 ). These data support protein synthesis as a tractable target in CRC, with the discovery of additional factors regulating these pathways only improving the potential to target protein synthesis in the clinic ( Knight and Sansom, 2021 ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, while rapamycin rapidly reduces phospho-eIF4E, MNK1-dependent eIF4E phosphorylation demonstrably occurs under prolonged treatment 13 . MNK1 blockade has additionally been demonstrated to sensitize rapalog-resistant glioma to inhibition of mTORC1 14,15 .…”
Section: Introductionmentioning
confidence: 99%